ANALISA PERBAIKAN POSTUR KERJA PADA PEMAKAI KOMPUTER DENGAN MEMAKAI METODE NORDIC BODY MAP (NBM) DAN RAPID OFFICE STRAIN ASSESSMENT (ROSA) - Feblidiyanti, Niera; Septianto, Andry (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
Complaints due to the high use of computers at work occur because of problems with equipment or facilities, workplace layout, working environmental conditions, or a combination of these factors. Complaints felt by workers can be minimized by knowing and identifying workers' work postures using the Nordic Body Map (NBM) questionnaire. The results of the Nordic Body Map (NBM) questionnaire were used to determine the condition of workers and the causes of complaints felt by workers based on the level of risk. Office ergonomics is the application of the science of ergonomics which includes the entire work environment and work tools used such as computers and chairs. The application of ergonomics in the office is more focused on the dangers of using computers. Hazards in the office are generally caused by incorrect work postures, repetitive movements and fixed positions for long periods of time. The dangers posed when working in an office are also influenced by the equipment used, such as a mouse, keyboard, monitor, computer desk and chair. Rapid Office Strain Assessment (ROSA) is one of the office ergonomics methods in which the assessment is designed to measure the risks associated with computer use and to determine the level of change action based on reports of worker discomfort. The results of the work posture assessment are pemakai 1 and 4 have a high level of risk so that it needs to be repaired immediately, pemakai 8 and 9 have a moderate risk level so that it needs to be repaired, pemakai 2, 3, 5, 6, 7, and 10 have a low risk level. so no need to repair.